The semantic conservation of architectural heritage: the missing values - Mohammad Sadegh Taher Tolou Del; Bahram Saleh Sedghpour; Sina Kamali Tabrizi (Heritage Science, 2020)
Abstract The conservation of the architectural heritage has enjoyed a long course of development over the recent decades. Conservation practice is based on the values offered by the architectural heritage resources for different individuals, groups, societies, and governments. Since there is no serious and comprehensive research on the semantic values, the present study was conducted to identify all the influential semantic values in the architectural conservation process and to determine the importance of each value based on the published literature. To this end, more than 100 scientific documents, statements, and charters were analyzed and then, 40 semantic values were identified. The snowball sampling method was used to select the papers. In this study, the qualitative content analysis was used to evaluate the relationship between the architectural heritage and conservation, and the quantitative content analysis was used to assess the relationship between the semantic values and conservation. According to the results of the content analysis, it can be concluded that the conservation of architectural heritage can be investigated and analyzed at three levels: people, experts, and governments, and the holistic conservation of the architectural heritage can be achieved only by the joint cooperation among all the three levels. Also, the results showed that the cultural value, economic value, historical value, and identity greatly influence the semantic conservation of the architectural heritage.